Sistem Pendukung Keputusan Pemilihan Guru Teladan Dengan Menggunakan Metode Composite Perfomance Index (CPI) - Nur Sakinah Tanjung; Putri Dani Adelina; Martina Klara Siahaan; Elvitrianim Purba; Joli Afriany (JURIKOM (Jurnal Riset Komputer), 2018)
The selection of exemplary teachers is expected to improve the spirit, motivation, and professionalism of selecting teacher model activities that occur usually only by using assessment which is based on personal analysis of the school parties SDN 003 Pagaran Tapah, so that there may be errors or mistakes. Based on that, then make a decision support system selecting exemplary teachers who can help the school in determining who the teacher who is entitled to be a model teacher. This system is built using Composite Performace Index Method (CPI). The results of this study are expected to be utilized by the school system to determine exactly who is entitled to be a model teacher by being based on several aspects, namely the ability of field of study, responsibility, creativity, communication.